2004
DOI: 10.1162/105474604774048234
|View full text |Cite
|
Sign up to set email alerts
|

Walking with and Without Walking: Perception of Distance in Large-Scale Urban Areas in Reality and in Virtual Reality

Abstract: The perception of distance when walking through an urban area depends on several factors. In addition to knowledge of the physical length of a route based on known parameters such as the walking speed and the time or number of steps, this paper also discusses external factors such as the visual appearance and details of the route and internal factors such as the physiological effort or emotional states during the walk. It is not clear which of the latter factors are stored in memory and are used to estimate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…While, residents in low density with larger buildings, lots and more open space would tend to underestimate distances. Several studies have concluded that age and gender have differed impacts on distance perception (Lee, 1970;Nasar, 1985;Popp et al, 2004). Low income group have a tendency to overestimate walking time rather than people with higher income perhaps as a result of less education or mobility (Burnett, 1978;Lowrey, 1973).…”
Section: Knowledgementioning
confidence: 99%
“…While, residents in low density with larger buildings, lots and more open space would tend to underestimate distances. Several studies have concluded that age and gender have differed impacts on distance perception (Lee, 1970;Nasar, 1985;Popp et al, 2004). Low income group have a tendency to overestimate walking time rather than people with higher income perhaps as a result of less education or mobility (Burnett, 1978;Lowrey, 1973).…”
Section: Knowledgementioning
confidence: 99%
“…The effect is however present on non-stereoscopic screens (Makaremi and N'Kaoua (2021); Popp et al (2004)), stereoscopic screens (Lin and Woldegiorgis (2017); Woldegiorgis and Lin (2017)) CAVEs (Piryankova et al (2013);Hofmann et al (2001)) and HMDs (Bodenheimer et al (2007); Gamberini et al (2008); Geuss et al (2012); Hiramoto and Hamamoto (2018); Napieralski et al (2011)). A comparison of older and more recent HMDs indicates a reduction of that effect on newer devices (Kelly et al (2017)), possibly as a consequence of increased display resolution and visual information (Ryu et al (2005)).…”
Section: Distance Perceptionmentioning
confidence: 99%
“…He produces an individual virtual space. Knowledge of the walking speed and the number of steps taken, the appearance of the environment and details, the effort and emotional states involved contribute to the production of the sense of distance (Popp et al, 2004). The studies of Bhalla and Proffit (1999) indicate that the sensation of the slope of the terrain may also be subjective, varying according to the load and clothing carried by the hiker, and that the perception of distance is greater on hills than on flat terrain.…”
Section: Walkingmentioning
confidence: 99%